Prevalence and sources of stress among medical students in school of medical sciences, Universiti Sains Malaysia. - Muhamad Saiful Bahri, Yusoff (2009)
The medical course has always been regarded as highly stressful. Excessive stress causes physical and mental health problems. Persistent stress will impair students' academic achievement, personal and professional development. Early detection and prevention of this condition will help in reducing the negative impacts of stress on medical students.The purpose of this study is to explore the nature of stress among medical students by determining the prevalence, sources, pattern, and determinant factors of stress. It is hoped that understanding the nature of stress will help medical teachers find ways to reduce and minimize the stress level of medical students during their study.This study utilized a cross-sectional design. All medical students in -the School of Medical Sciences, Universiti Sains Malaysia were taken as subjects in this study. Data collection was done two months after the academic session of 2008/2009 started. A validated questionnaire was used. School and ethical committee clearance were obtained prior to the start of the study. Data were analysed using Statistical Package for Social Sciences (SPSS) version 12.761 (72%) respondents participated in this study. The prevalence of stress among medical students in School of Medical Sciences, Universiti Sains Malaysia was 29.6%. The top 10 stressors were academic-related. Prevalence of stress for the first-, second-, third-, fourth- and fifth-year students were 26.3%, 36.5 %, 31.4%, 35.3% and 21.9% respectively. Year of study was the only significant determinant factor of stress among medical students (LR-statistics = 527.18, p-value = 0.034).The prevalence of stress among medical students in USM is high. Academic related problems were the major stressors among medical students. Year of study was the factor most significantly associated with medical students' stress level. There was bimodal pattern of stress level throughout the year of study, peaking at the second and fourth years of study.